2022
DOI: 10.3389/fpubh.2022.831312
|View full text |Cite
|
Sign up to set email alerts
|

Financing Costs and Health Effects of Air Pollution in the Tri-City Agglomeration

Abstract: This paper examines the relationship between the presence of air pollution and incidence of selected respiratory diseases in the urban population of the Tri-City agglomeration. The study takes into consideration the specific character of the region, relating to coastal, and port-based shipping. Three research hypotheses formulated the study. General regression models were used to identify the health effects of air pollution and developed health costs were calculated in relation to the treatment of diseases. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
7
0
1
Order By: Relevance
“…The authors also point to effects in the form of reduced forced expiratory volume within the first second of expiration (FEV 1 ) and forced vital capacity (FVC). Similar results (however, limited to one agglomeration) were presented in the results of the study by Czechowski et al [ 29 ]. It has been shown that air pollution and climatic conditions in the Tricity (an agglomeration located in northern Poland, on the Baltic coast) exacerbate the symptoms of bronchial asthma, also increasing the number of exacerbations of chronic obstructive pulmonary disease (COPD) and pneumonia.…”
Section: Introductionsupporting
confidence: 90%
“…The authors also point to effects in the form of reduced forced expiratory volume within the first second of expiration (FEV 1 ) and forced vital capacity (FVC). Similar results (however, limited to one agglomeration) were presented in the results of the study by Czechowski et al [ 29 ]. It has been shown that air pollution and climatic conditions in the Tricity (an agglomeration located in northern Poland, on the Baltic coast) exacerbate the symptoms of bronchial asthma, also increasing the number of exacerbations of chronic obstructive pulmonary disease (COPD) and pneumonia.…”
Section: Introductionsupporting
confidence: 90%
“…Air pollution has been associated with various socio-economic impacts. Various researchers have linked air pollution with health issues [37][38][39][40][41][42], mortality rate [43][44][45]39], labor loss [38], social factors [46], economic burden [38], or financial/economic losses [47][48][49].…”
Section: Expected Benefits From the Improvement Of Environmental Impa...mentioning
confidence: 99%
“…In addition to significant burdens on healthcare providers, huge economic losses result from health-related implications of air pollution [47]. Some scholars [48] have reported that financial losses are associated with the treatment of diseases that are caused by air pollution. Some researchers [38] related air pollution to public health issues, loss of labor, and economic burden in the long run.…”
Section: Expected Benefits From the Improvement Of Environmental Impa...mentioning
confidence: 99%
“…In this regard, it would be necessary to expand the infrastructure that takes road traffic out of the agglomeration. The quality of the atmosphere in Gda ńsk would also be improved by excluding resource vehicles equipped with diesel engines and the wider adoption of hybrid and electric cars [16]. In addition to the land traffic, Gda ńsk is also affected by the shipping industry by having, in the direct area of the city, the biggest seaport in Poland, with over 52 million tons of turnover yearly and 5000 ships calling on the port yearly.…”
Section: Introductionmentioning
confidence: 99%